Early Experience With Automatic Pressure-Controlled Cerebrospinal Fluid Drainage During Thoracic Endovascular Aortic Repair. (June 2015) - Kotelis, Drosos; Bianchini, Claudio; Kovacs, Bence; Müller, Thomas; Bischoff, Moritz; Böckler, Dittmar
Purpose: To report initial experience with automatic pressure-controlled cerebrospinal fluid drainage (CSFD) during thoracic endovascular aortic repair (TEVAR).Methods: A prospective nonrandomized study enrolled 30 consecutive patients (median age 68 years, range 42–89; 18 men) who underwent TEVAR between March 2012 and July 2013 and were considered to be at high risk for postoperative spinal cord ischemia (SCI), fulfilling 2 of the following criteria: stent-graft length >20 cm, left subclavian artery coverage, and previous infrarenal aortic repair. All patients received perioperative CSFD via the LiquoGuard system. The protocol aimed for a CSF pressure of 10 mm Hg and duration of CSFD of 3 or 7 days in asymptomatic or symptomatic patients, respectively. Muscle strength of the lower extremities was assessed with the Oxford muscle strength grading scale.Results: Completion of the CSFD protocol was achieved in 26 (87%) of 30 patients. CSFD was prematurely stopped due to catheter dislocation in 1 patient and bloody spinal fluid in 3 patients. CSFD was performed for a median of 3 days (range 1–7). Median total CSFD volume was 714 mL (range 13–2369), with a median 192 mL drained per 24 hours. The SCI rate was 3% (1/30). CSFD-related complications were observed in 33% of the patients: 1 fatal intracranial hemorrhage, 3 bloody spinal fluid episodes, 3 persistent CSF leaks requiring epidural blood patch, and 3 post lumbar puncture headaches. Mortality during a median follow-up of 16 months (range 10–25) was 3% (1/30).Conclusion: Prophylactic CSFD was associated with a low SCI rate in a high-risk patient collective undergoing TEVAR. Monitoring and drainage by an automatic modus was feasible, reproducible, and reliable but associated with relevant drainage-associated complications.